"A very basic view of feminism": feminist girls and meanings of (celebrity) feminism. Issue 7 (3rd October 2021) - Jackson, Sue
ABSTRACT: Feminist scholarship has richly critiqued the burgeoning of popular feminism across multiple media platforms in recent years. Representing a particular visibility of popular feminism, celebrity feminism has re-ignited questions about what constitutes a "legitimate" feminist. But what might the mediated visibility of celebrity feminism mean and make possible for media audiences? Observing the dearth of audience studies, several scholars highlight the need to investigate audience meanings of mediated feminisms. Given that young celebrities such as Amandla Stenberg often (re)present the popular "fresh face" of feminism and that media provide a key resource for girls to learn about feminism, such investigation is particularly salient for teenage girls. This paper draws on research with young feminists to explore ways they make sense of celebrity feminism in relation to their own understandings of feminism and feminist subjectivity. Analyses show how celebrity feminism functions as a discursive tool for girls' negotiation of the borders that constitute self and others as feminist subjects (or not). Although girls constructed celebrity feminists as potentially useful in drawing people into feminism, they also critiqued celebrity feminism as "trendy", apolitical and "basic", offering little more than a rhetoric of equal rights, devoid of intersectional values and lacking political activism.